Dari Forum ke Kampus Pengaruh ASEAN Tourism Forum dalam Mengembangkan Pendidikan Pariwisata di Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta - Joko Triyono; Agung Yuliyanto; Dwi Yoso Nugroho (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2024)
The ASEAN Tourism Forum (ATF) is a strategic platform for Southeast Asian countries to collaborate in developing the tourism industry. This study aims to explore how ATF influences the development of tourism education at the Ambarrukmo Tourism College in Yogyakarta. This study uses a qualitative approach with a case study method, involving interviews with institutional managers, lecturers, and students, as well as analysis of related documents. The results of the study indicate that ATF has a positive impact through several aspects: first, improving the curriculum to be more relevant to the trends and needs of the regional tourism industry; second, improving the capabilities of lecturers through training and workshops held in the ATF series; third, opening up opportunities for international cooperation that expand academic and practical networks for the institution. These findings indicate that participation in ATF contributes significantly to the development of the quality of tourism education at STP Ambarukmo, connecting theory with practice and preparing students to face global challenges in the tourism industry. This study recommends increasing active participation in similar forums to take advantage of more learning and collaboration opportunities.